Daya Saing Komoditas Unggulan Tanaman Pangan Kota Padang - Ilham Martadona (Jurnal Multidisiplin Madani, 2022)
Food crops are commodities that have an important role in regional economic development because they have comparative and competitive advantages. The city of Padang is one of the centers for the development of food crops in West Sumatra Province, especially rice plants. The purpose of the study was to calculate food crop commodities as the leading commodity in the city of Padang, and measure the magnitude of the development (trend) of the leading commodity of food crops in the city of Padang. Secondary data is used in the study, namely rice production data for 2016-2020.analysis Location Quetion and Least Square Method were used as data testing tools. The results showed that the leading commodity of food crops was rice in the city of Padang. Meanwhile, the trend of rice production tends to decrease production by 4.367 tons (2021-2025).